Dual oxidases - Donkó, Ágnes (The Royal Society, 2005)
Reactive oxygen species (ROS) have an important role in various physiological processes including host defence, mitogenesis, hormone biosynthesis, apoptosis and fertilization. Currently, the most characterized ROS-producing system operates in phagocytic cells, where ROS generated during phagocytosis act in host defence. Recently, several novel homologues of the phagocytic oxidase have been discovered and this protein family is now designated as the NOX/DUOX family of NADPH oxidases. NOX/DUOX enzymes function in a variety of tissues, including colon, kidney, thyroid gland, testis, salivary glands, airways and lymphoid organs. Importantly, members of the enzyme family are also found in non-mammalian species, including Caenorhabditis elegans and sea urchin. The physiological functions of novel NADPH oxidase enzymes are currently largely unknown. This review focuses on our current knowledge about dual oxidases.